Cyberloafing Behavior: The Determining Factors Influenced by Workload and Work-Related Stress Among Healthcare Workers - Dian Wahyuningsih (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2026)
In the digital age, the ubiquity of internet access in workplaces has led to a rise in cyberloafing behaviors, particularly in high-pressure environments such as healthcare. In hospitals, where stress and workload are high, healthcare workers are more likely to engage in non-work-related online activities during work hours, which can negatively affect patient care and employee productivity. This study investigates the influence of workload and work stress on cyberloafing behavior among health workers. Cyberloafing is a prevalent behavior in the digital work era, often manifesting when employees use the internet for non-work-related purposes during working hours. Health workers, in particular, are vulnerable due to high demands and emotional pressure. The research uses a quantitative method with a descriptive and verificative approach. The population comprises 150 health workers, with 110 samples selected via purposive sampling. Data was collected using a questionnaire and analyzed using linear regression. The results showed that workload has a significant positive influence on cyberloafing behavior with a contribution of 40.9%, and work stress has a significant effect with a contribution of 42.2%. Simultaneously, workload and work stress influence cyberloafing by 83.1%. These findings highlight the need for improved workload management and stress coping strategies to minimize cyberloafing and maintain service quality in hospitals.